Suicides in the Centre of Portugal: seven years analysis - Dias, Daniel (2014)
As one of the more specific and distinctive problems of human beings, suicide has been investigated with increasing attention all over the world. Several risk factors have been described as well as limitations arising from their study. The World Health Organization estimates that this scourge affects one million people annually, which corresponds to one death every 40 s worldwide. According to recent studies, Portugal, despite the good rates (10 suicide deaths per 100,000 inhabitants), had shown an increasing trend among younger people. This work aims to characterize the evolution of the suicidal profile autopsied at the Forensic Pathology Department of the Centre Branch of the National Institute of Legal Medicine and Forensic Sciences of Portugal, analyzing several variables: age, gender, marital status, employment status, suicidal methodology, toxicological analysis and some conditions/behaviors regarding personal history (alcoholism, suicidal ideation, suicide attempts, physical illness, psychiatric disorder). All the autopsies from the 1 January, 2003 to 31 December, 2009 were analyzed. The suicide profile achieved corresponded to a man (77%), aged between 65 and 74 years old (20.4%), married (54.5%), employed, who committed suicide by hanging, in September, May or February. Clinical records include an organic health problem or psychiatric one, in addition to risk behaviors such as alcoholism, suicidal thoughts or suicide attempts. The number of suicides autopsied at the Centre Branch has increased, resembling the profile to the result of many other authors. However, new medical and social developments place hanging as the favorite suicide method in our study. Many barriers remain to overthrow but several prevention programs begin to be designed and implemented. Future evaluations and interventions at the social and medical level, including the death certification process, will be fundamental to a better realistic understanding of this phenomenon.